THE INFLUENCE OF BOARD ALLOWANCE AND GENDER DIVERSITY ON ESG REPORTING QUALITY IN THE AMMAN STOCK EXCHANGE (ASE) - Srouji, Menazel Fatehi; Ibrahim, Suraiya; Yusoff, Wan Sallha (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
Purpose: This article conceptually investigates the influence of two critical corporate governance mechanisms—Board of Directors’ Allowance (Compensation) and Board of Directors’ Gender Diversity—on the quality of Environmental (E), Social (S), and Governance (G) Reporting among companies listed on the Amman Stock Exchange (ASE). The study leverages established theories such such as Agency Theory, Stewardship Theory, and Resource Dependence Theory to develop a conceptual framework. Methodology: The study proposes a hypothetical methodology utilizing panel data regression and content analysis of sustainability reports from companies listed on the ASE20 index over a five-year period (e.g., 2020–2024). Content analysis would be used to develop a disclosure index based on GRI/ISSB standards. Findings: The synthesized findings anticipate that both independent variables are positively associated with enhanced ESG disclosure quality. Higher board allowance is expected to attract the necessary expertise for complex ESG oversight, while greater gender diversity is hypothesized to introduce perspectives that foster transparency and accountability, particularly in the Social and Governance dimensions. Conclusion: The quality of ESG Reporting in the Amman Stock Exchange is significantly shaped by the internal dynamics of the Board of Directors. The study offers crucial implications for Jordanian regulators and corporate boards, emphasizing the strategic role of board composition in advancing corporate sustainability and market transparency.